Antimicrobial resistance in community and nosocomial Escherichia coli urinary tract isolates, London 2005 - 2006 - Wareham David W; Krahe Daniel; Bean David C (BMC, 2008)
Abstract Background Escherichia coli is the commonest cause of community and nosocomial urinary tract infection (UTI). Antibiotic treatment is usually empirical relying on susceptibility data from local surveillance studies. We therefore set out to determine levels of resistance to 8 commonly used antimicrobial agents amongst all urinary isolates obtained over a 12 month period. Methods Antimicrobial susceptibility to ampicillin, amoxicillin/clavulanate, cefalexin, ciprofloxacin, gentamicin, nitrofurantoin, trimethoprim and cefpodoxime was determined for 11,865 E. coli urinary isolates obtained from community and hospitalised patients in East London. Results Nitrofurantoin was the most active agent (94% susceptible), followed by gentamicin and cefpodoxime. High rates of resistance to ampicillin (55%) and trimethoprim (40%), often in combination were observed in both sets of isolates. Although isolates exhibiting resistance to multiple drug classes were rare, resistance to cefpodoxime, indicative of Extended spectrum β-lactamase production, was observed in 5.7% of community and 21.6% of nosocomial isolates. Conclusion With the exception of nitrofurantoin, resistance to agents commonly used as empirical oral treatments for UTI was extremely high. Levels of resistance to trimethoprim and ampicillin render them unsuitable for empirical use. Continued surveillance and investigation of other oral agents for treatment of UTI in the community is required.